Risk Factors Pneumonia Occurrence In The Work Area Of Puskesmas Rao Pasaman Regency Year 2017 - Sari, Yulia Puspita; Gustin, Rahmi Kurnia (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
Pneumonia is the premier killer of toddlers in the world. Ministry of Health RI prevalence of Pneumonia in infants in Indonesia in 2014 range between 23% -27%. Cases of Pneumonia in the Work Area Rao PuskesmasPasaman District in 2016 found 20 cases. This study aims to determine the risk factors of Pneumonia incidence in infants in the Rao Pasum Community Health Center Working Area 2017, including, Exclusive Breast, Nutritional Status, Drug Use Mosquito Fuel, and Use of Cooking Fuel. The design of this study used the case-control study. The research started from March to September 2017 in the Work Area of Puskesmas Rao Pasaman District. The case population as many as 20 cases and the control in this research is the mother who has a toddler who does not suffer from Pneumonia. The sample of the case using formula as many as 11 cases with the technique of simple random sampling and control sample 11 respondents taken by purposive sampling. Data were analyzed using chi-square (95% CI, Î± = 0,05). Results of analysis of exclusive breastfed variables with the incidence of pneumonia in toddlers in get p = 0.003; OR = 45, Nutritional status was obtained p-value = 0,024; OR = 17,500, The use of Mosquito Drugs obtained p = 0,659; OR = 2,222, and Cooking Usage result p = 1,000; OR = 1.524.It can be concluded that Exclusive Breast Milk and Nutritional Status are statistically related and a risk factor for the incidence of Pneumonia (p <0.05), while the Use of Mosquito and Cooking Fossil is statistically unrelated and is a risk factor for the occurrence of Pneumonia (p> 0, 05). It is suggested to Rao PuskesmasPasaman to increase P2 ISPA program in prevention and prevention of pneumonia disease in under-fives.